2004
DOI: 10.1152/ajpgi.00398.2003
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical decrease of mitochondrial DNA deletions in epithelial cells of active ulcerative colitis patients

Abstract: Fukushima, Kouhei, and Claudio Fiocchi. Paradoxical decrease of mitochondrial DNA deletions in epithelial cells of active ulcerative colitis patients. Am J Physiol Gastrointest Liver Physiol 286: G804-G813, 2004; 10.1152/ajpgi.00398.2003.-Ulcerative colitis (UC) is a condition characterized by chronic inflammation targeted at the epithelial layer. In addition to being involved in immune phenomena, UC epithelial cells exhibit decreased oxidation of butyrate, downregulation of oxidative pathway regulatory genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…In case of human oocytes it has been confirmed that age exhibits the only significant correlation with the presence of the 4977 bp deletion, while other parameters like smoking or early follicular phase FSH did not reveal any correlation (Chan et al, 2005). In recent years, a number of carefully conducted studies reported, that the level of the 4977 bp deletion is not increased in different tumour tissues (Dani et al, 2004;Dai et al, 2006;Ye et al, 2007) and in conditions associated with chronic inflammation like ulcerative colitis (Fukushima and Fiocchi, 2004). Though our data display a great variability even in individuals of the same age group, the large pool of data may help to discriminate between physiological ageing and pathological conditions associated with accelerated ageing.…”
Section: Discussionmentioning
confidence: 92%
“…In case of human oocytes it has been confirmed that age exhibits the only significant correlation with the presence of the 4977 bp deletion, while other parameters like smoking or early follicular phase FSH did not reveal any correlation (Chan et al, 2005). In recent years, a number of carefully conducted studies reported, that the level of the 4977 bp deletion is not increased in different tumour tissues (Dani et al, 2004;Dai et al, 2006;Ye et al, 2007) and in conditions associated with chronic inflammation like ulcerative colitis (Fukushima and Fiocchi, 2004). Though our data display a great variability even in individuals of the same age group, the large pool of data may help to discriminate between physiological ageing and pathological conditions associated with accelerated ageing.…”
Section: Discussionmentioning
confidence: 92%
“…Rho GDI alpha (Rho GDP-dissociation inhibitor 1), L-lactate dehydrogenase A, etc.). In ulcerative colitis patients, forty differentially expressed proteins were identified among which thirteen were associated with energy metabolism, which is in line with chronic intestinal inflammation being characterised by energy deficiency and alteration of the oxidative metabolism of epithelial cells (185,186) .…”
Section: Biomarkers: Proteins and Peptides As Indicators Of Health Anmentioning
confidence: 62%
“…During the last years, accumulating evidence implicated ER UPR at the epithelial cell level in promotion and perpetuation of intestinal inflammation,24, 128, 129 and at the same time, it has been repeatedly suggested that chronic intestinal inflammation represents an energy‐deficiency disease involving mitochondria and featuring alterations in epithelial cell oxidative metabolism 25, 130. Inflammation and ER stress are linked at many levels, since inflammation is characterized by the production of large amounts of proteins such as cytokines or chemokines and, furthermore, ER UPR signaling can directly intersect with inflammatory pathways including NF‐κB, JNK, TLR‐mediated signaling and production of ROS 131–134.…”
Section: Er Upr and Mitochondrial Dysfunction In Ibdmentioning
confidence: 99%
“…Various metabolically driven and inflammatory diseases feature activated ER UPR1–3, 7 and both ER‐ and mtUPR are associated with IBD24 14. Also, mitochondrial dysfunction and alterations in energy metabolism in general have been implicated during the onset and course of neoplasia, metabolic diseases, and inflammation 21, 23, 25. Beyond their well‐established functions in cell metabolism and during apoptosis, mitochondria have gained increasing attention for their role in innate immune signaling 26–29.…”
mentioning
confidence: 99%